2007
DOI: 10.1007/s11419-007-0020-z
|View full text |Cite
|
Sign up to set email alerts
|

An automated on-line method for simultaneous analysis of phenothiazines in human serum by high-performance liquid chromatography/sonic spray ionization mass spectrometry using backflush column switching

Abstract: An automated on-line method for simul taneous analysis of fi ve phenothiazine drugs by high-performance liquid chromatography (HPLC)/sonic spray ionization mass spectrometry (SSI-MS) has been established, using backfl ush column switching. A 400-µl portion of serum sample diluted 81-fold with distilled water was subjected to the on-line system. In the system, an Oasis HLB cartridge was used as the precolumn for extraction; large molecules such as proteins in serum were discarded by use of distilled water conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
(39 reference statements)
1
3
0
1
Order By: Relevance
“…The LODs for the optimized method were also measured, based on a S/N greater than 3. It was found that LODs between 0.7 and 1.5 ng/mL for CPZ and TFP, respectively, comparable to those values reported by other authors 9, for which there were no carryover or interferences, were detected from blank assays.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The LODs for the optimized method were also measured, based on a S/N greater than 3. It was found that LODs between 0.7 and 1.5 ng/mL for CPZ and TFP, respectively, comparable to those values reported by other authors 9, for which there were no carryover or interferences, were detected from blank assays.…”
Section: Resultssupporting
confidence: 86%
“…In these methods, the sample pretreatments such as liquid–liquid extraction, solid‐phase extraction and protein precipitation are usually required to remove proteins and other impurities contained in biological matrices. These methods including time and solvent consuming multistep sample pretreatments are unsuitable in the field of emergency medicine, which demands rapid and sensitive detection 9. Among the new preconcentration procedures found in the recent literature, the use of microsorption techniques such as solid phase microextraction and liquid phase microextraction 10, 11 shows an increasing demand.…”
Section: Introductionmentioning
confidence: 99%
“…Phenothiazine derivatives are a group of basic substances which have been widely used as antipsychotic, antiparkinsonian, and antihistaminic drugs [1]. Biochemically, they are antagonists of dopamine receptors whose action mechanism is based on the blockade of nervous impulses from the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Так, відповідно до даних джерел для визначення та оцінки прохлороперазину у формі субстанції та лікарських форм авторами використано ряд аналітичних методів для ідентифікації та кількісного визначення при проведенні фармацевтичного аналізу, вивчення фармакокінетики, дослідження біоеквівалентності. Зокрема, гравіметричний [35], спектрофотометричний [35,36], ТШХ [37], ВЕРХ [38][39][40][41], кондуктометричний [42], вольтамперометричний [43], капілярний електрофорез [44], РХ-MС методи [45,46].…”
Section: результати та їх обговоренняunclassified